Neuroprotective effect of Vanillin on hypoxic-ischemic brain damage in neonatal rats - Xiao-Bing Lan (Biomedicine & Pharmacotherapy, 2019)
Neonatal hypoxic-ischemic brain damage (HIBD) is a leading cause of death and perpetual neurological dysfunction in neonates. Vanillin (Van), a natural phenolic compound with neuroprotective properties, exerts neuroprotection on a gerbil model of global ischemia by inhibiting oxidative damage. This study aimed to explore the potential neuroprotective roles of Van in neonatal rats suffering from hypoxic-ischemic (HI). An HI model of 7-day-old SD rats was induced by left carotid artery ligation followed by exposure to 8% oxygen (balanced with nitrogen) for 2.5 h at 37 °C. At 48 h after intraperitoneal injection with Van (20, 40, and 80 mg/kg) or saline, neurobehavioral function, cerebral infract volume, brain water content, and histomorphological changes were performed to evaluate brain injury. Transmission electron microscopy and immunoglobulin G (IgG) staining were conducted to evaluate the integrity of the blood-brain barrier (BBB). The levels of oxidative stress and tight junction proteins, as well as the activities of matrix metalloproteinases (MMPs), were also determined in the ipsilateral hemisphere. Results showed that Van post-treatment significantly ameliorated early neurobehavioral deficits, decreased infarct volume and brain edema, as well as attenuated histopathologic injury and IgG extravasation. Furthermore, Van markedly increased the activities of endogenous antioxidant enzymes and decreased malondialdehyde content. Meanwhile, the activation of MMP-2 and MMP-9 induced by HI was partially blocked by Van. Finally, Van obviously increased the expression of ZO-1, Occludin, and Claudin-5 compared with the HI group. Collectively, Van can provide neuroprotective effects against neonatal HIBD possibly by attenuating oxidative damage and preserving BBB integrity.